Egypt's mysterious pyramids an Isabel Soto archaeology adventure - Biskup, Agnieszka; Stewart, Roger (Minn. : Capstone Press, 2012)
In graphic novel format, follows the adventures of Isabel Soto as she discovers the secrets about Egypt's great pyramids"--Provided by publisher.